Penguatan Kerja Sama Tim melalui Nilai Pancasila dan Proyek Pengolahan Sampah pada Siswa Kelas V Sekolah Dasar - Siti Aisyah; Anggiena Najma Zafira; Riby Ramadhani; Tobias Embong Raharjo Syam; Nabila Faliha; Ayla Azzuhra; Naomi Dias Laksita Dewi; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Teamwork skills represent a social competency that must be developed from the elementary school level. Preliminary observations in Grade V of an elementary school revealed that some students remained less active in group discussions, demonstrated suboptimal teamwork abilities, and exhibited low environmental awareness. The activity aimed to strengthen students' teamwork skills through Pancasila values education integrated with a waste management project. Implementation took place at SD Negeri Pekalangan 2, Bondowoso, involving 30 fifth-grade students using a descriptive qualitative approach supported by simple quantitative data. Applied methods included learning Pancasila values using spinner-based interactive media, group-based organic and inorganic waste processing projects, and outing class activities. Data collection was conducted through pretest–posttest social skills questionnaires, structured observations, and documentation, which were then analyzed descriptively. Results demonstrated improvements in students' teamwork and social skills, with student activeness increasing from 55% to 90%, teamwork from 60% to 88%, empathy from 58% to 85%, and environmental awareness from 50% to 85%. Observations also revealed that students became more confident in expressing opinions, collaborated more effectively in groups, and demonstrated greater concern for the school environment. The activity proved effective in strengthening students' teamwork skills through the integration of Pancasila values and waste management projects. The program can serve as an alternative project-based learning approach for elementary school teachers to support character education and the Pancasila Student Profile.